PADRONIZAÇÃO E USO DA ARMADILHA LUMINOSA SILVA À BASE DE LEDS (LIGHT-EMITTING DIODES) NAS CAPTURAS DE MOSQUITOS ANOFELINOS NO ESTADO DO MARANHÃO. - ARAUJO, Eudimara Carvalho de (2021)
Malaria is an infectious disease transmitted to man after exposure by the bites of infected anopheline females. For a long time, malaria has been a persistent health problem with high mortality and morbidity occurring mainly in the developing countries. As the transmission cycle of malaria varies worldwide, entomological surveillance is an important component in the fight against malaria. Thus, several collecting tools, such as the Center for Disease and Control and Prevention light trap (CDC), the light trap (HP), the BioGents® Sentinel and Malaria trap (BG-Sentinel; BG-Malaria) have been employed extensively. Such traps have some disadvantages such as high costs, need of chemical odors to attract mosquitoes and the problems of damaging the collected specimens, causing difficulties to species identification. Hence, this research aims at standardizing a passive light trap, the Silva Trap (ST), for the captures of anopheline mosquitoes in peridomicile and forest environments. This light trap was efficiently used for sampling anopheline mosquitoes in pig pens, but its efficiency in peridomicile and forest areas needs to be evaluated. Thus, in the first moment, three LED colors (blue, 470 nm, 15,000 mcd; green, 470 nm, 20,000 mcd; ultraviolet, 395 nm, 3,000 mcd) had their efficiency as light sources for sampling anopheline mosquitoes in the peridomicile settings evaluated. In the second moment, different heights (0,5m; 1,0m; 1,5m; 2,0m) for a better use of the Silva trap were evaluated. In the third moment, the most attractive color and the best height for installing the Silva trap were chosen to capture anopheline mosquitoes in a forest environment. In this later case, HP light traps were used as “control”. In total, 9,009 specimens and nine species were collected: Anopheles triannulatus s.l, An. argyritarsis, An. goeldii, An. rangeli, An. galvaoi, An. evansae, An. darlingi, An. mediopunctatus and An. neomaculipalpus. In the first moment, a total of 3,750 specimens was captured and the green LED attracted 48.21% (58.32± 13.93followed by the bleu LED (44.93%, 56.17 ± 14.44) and ultraviolet (6.85%, 9.88 ± 1.74). In the second moment, 2,955 anopheline mosquitoes were captured, with the following results: 0,5m (17.63%, 30.65± 4.79/media ± SEM), 1,0 m (28,29%, 44± 7.61), 1,5 m (32,04%, 47.35± 8.53) and 2,0 m (22,03%, 34.26± 7.60). In the last moment, the Silva trap, with green LED, attracted 38,88% (59.73± 6.69), followed by the HP with green LED 36,37% (55.87± 11.43) and HP with incandescent light 24,73% (38±6.54). The Silva trap with the green LED and deployed at 1,5m above soil was the most efficient mode of operation of the Silva light trap, with a significant statistical result only observed between the Silva trap with a green LED and the HP with incandescent light, demonstrating that the use of the Silva trap and LEDs in the monitoring and, possibly, controlling programs should be considered.